Easter flower! what would you here? - Balslev-Clausen, Peter (Grundtvig-studier, 2014)
Easter flower! what would you here? Anthology of songs and hymns by N.F.S.Grundtvig. Translated into English by John Irons, Selected and edited Anne-Marie Mai & Jørn Henrik Petersen, Odense, Syddansk Universitetsforlag,2013. 83 pp.